Sociological Analysis of Quality of Life of Senior Citizens: A Study of Old Age Homes (Journal of Social Sciences Review, 2025)
The present study explores the sociological analysis of quality of life of senior citizens that come to be related with demographic shift. Quality of life is defined often with equally objective and subjective measurements. Majority of senior citizens evaluate their quality of life on the basis of substantial circumstances, physical and emotional wellbeing, dependency and social network. Earlier studies depict senior citizens are met with many challenges alternating from deprived admittance to health care, negligence by friends and family that might affect quality of life. The current research basically assesses the relationship between physical and emotional wellbeing and level of satisfaction among seniors at the age of 60 and above. Researcher collected the data from 116 participants through quantitative research design under simple random sampling, participants including 76 males and 40 females nominated from three areas Rawalpindi, Islamabad and Wah-Cantt. Results suggests negative but weak correlation among variables such as physical or emotional wellbeing and level of satisfaction. Findings advocates that quality of life of senior citizen is better for those who exist in old age home. Moreover, old age home can improve senior citizen’s quality of life through generating cohesive social setting and also encouraging societal participation in healthy and recreational activities.
Keywords: Senior Citizen; Old Age Home; Quality of Life; Physical Wellbeing; Emotional Wellbeing; Satisfaction